HUBUNGAN MASA KERJA DENGAN KAPASITAS VITAL PARU OPERATOR EMPAT STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) KOTA YOGYAKARTA - Setiawan, Irvan; Hariyono, Widodo (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2011)
Background: Motor vehicles contributed almost 100 percent plumbum, 70,5 percent of carbon monoxide, 8,89 percent oxide nitrogen, 18,34 percent hydro carbon and 1,33 percent particles. Many pollutants would cause bad effect especially to respiratory system. Air pollution in Yogyakarta city, were above norml threshold of air qualiy standards. One point area with with high air pollutionis in SPBU. The officers also had high risk to exposed danger chemicals especially plumbum by gaso-line and gas emissions of motor vehicle that waiting queue refueling or vehicle departing after refu-eling. The longer someone worked so the more he has exosed the danger that generated by work environment. The purpose of this study was to determine the relation between work period with lung vital capacity operator in four public refueling stations Yogyakarta city. Methods: this study was analytic observational with kuantitatif methods. Design used cross sctonl. The sample of this study were operator four public refueling stations amount 43 persons. The measurements of lung vital capacity used electric spirometer and themeasure of work period used questionnaire. Data analsys used univariate and bivariate. Result: there was a significant relation between work period with lung vital capacity operator in four public refueling Yogyakarta city with significancy value (p) amount 0,018 with p=0,018,<?=005, so Ho which states there is no relationship between work periods with lung vital capacity in four public refueling stations rejected. Ha which states there is relationship between work periods with lung vtal capacity I four public refueling stations accepted Conclusion: work periods had significant relation to lung vital capacity operator in four public sta-tions in yyogyakarta city. Keywords: work periode, lung vital capacity, public refueling station operator